ADAPTASI ANATOMIS POHON PADA ROOF GARDEN (Studi Kasus: Kondominium Taman Anggrek, Jakarta) - Andini Arisanti; Aris Munandar; Theresia Prawitasari (http://arl.faperta.ipb.ac.id/, 2010)
Roof garden can be interpreted as garden residing in a roof top. Not all plants can survive living on roof tops. The plants which can be planted in roof gardens have to be adaptive to high speed of wind, extreme temperature, and high intensity of irradiation. Objective of this research is to learn environmental influence of stress that induced anatomical adaptation of tree spesies (i.e Bauhinia sp., Erythrina christagalli, Mussaenda sp.and Wodyetia bifurcata) at roof garden in Taman Anggrek condominium, Jakarta.Plants which are planted in normal garden will response differently with the ones in roof garden. Different plants have their own adaptation form that can be visible from their anatomy. The result of this research is Bauhinia sp. shows a better adaptation in roof garden, Wodyetia bifurcata can adapt well, while Erythrina christagalli and Mussaenda sp. cannot adapt well in roof garden. A simple visualisation value concluded that Bauhinia sp. has a better shape, then the others. After all, this study should be completed with research of more physiological pattern and a complete assesment of tree visualisation.